2015
DOI: 10.2174/1574892810999150827153642
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis Markers in Gynecological Tumors and Patents for Anti- Angiogenic Approach: Review

Abstract: The formation of a tumor-associated vascular network is an important step in understanding the stages of tumor progression. This review aims to highlight the main markers of induction, proliferation and inhibition of angiogenesis, as well as the quantification of microvessel density, correlated with preclinical and clinical research in gynecologic cancers and also discussed related patents. Studies show that in the most advanced cases of gynecological cancers, biomarkers such as VEGF (Vascular Endothelial Grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…It is well-known that activated MMP-2 contributes to the angiogenic process by remodeling the basement membrane to allow sprouting and liberating matrix-bound angiogenic factors [28]. In addition, COX-2 overexpression in colon carcinoma cells increases their angiogenicity, as shown by an increased ability to stimulate endothelial cell migration and tube formation by producing prostaglandins such as prostaglandin E2 and inducing pro-angiogenic factors such as basic fibroblast growth factor [2931].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that activated MMP-2 contributes to the angiogenic process by remodeling the basement membrane to allow sprouting and liberating matrix-bound angiogenic factors [28]. In addition, COX-2 overexpression in colon carcinoma cells increases their angiogenicity, as shown by an increased ability to stimulate endothelial cell migration and tube formation by producing prostaglandins such as prostaglandin E2 and inducing pro-angiogenic factors such as basic fibroblast growth factor [2931].…”
Section: Discussionmentioning
confidence: 99%
“…Stromal expression of MMP-7 was higher also in serous compared to mucinous tumors; while the expression of MT1-MMP, MMP-7 and -9 was similar in benign and borderline tumors compared to control group [ 191 ]. A recent study also showed higher expression of VEGF, MMPs, CD105 (Endoglin), TIMPs and VASH (Vasohibin) on advanced gynaecological cancers compared to healthy individuals [ 192 ]. A screening study using an orthotopic ovarian carcinoma model in nude mice recently demonstrated that the mRNA levels of TIMP-2, MMP-2 and other ovarian cancer associated proteins such as cytokeratin -7 (CK-7), cancer antigen-125 (CA-125), tumor suppressor P53 and survivin, were significantly higher in cancer tissue than the middle paraneoplastic tissue and remote paraneoplastic tissue and normal ovarian tissue [ 193 ].…”
Section: Metzincins and Timps In Ovarian Cancermentioning
confidence: 99%
“…pH changes for values higher than 4.5 are easily found in women who presents bacterial vaginosis, being the immunological response in this case and for HPV infection are similar, with an expressive increase of cytokines for both. In this sense many studies in the literature abording immune response in different grades of cervical lesions, thus understanding how the immune system behaviour during HPV infection with or without vaginosis [13].…”
Section: Resultsmentioning
confidence: 99%